Prevalence and distribution of unintended pregnancy: the Understanding Fertility Management in Australia National Survey - Heather Rowe; Sara Holton; Maggie Kirkman; Christine Bayly; Lynne Jordan; Kathleen McNamee; John McBain; Vikki Sinnott; Jane Fisher (Elsevier, 2016)
Abstract Objective: Mistimed, unexpected or unwanted pregnancies occur in Australia, despite widespread contraception use. The objective was to estimate prevalence and ascertain modifiable social factors for prevention of unintended pregnancy. Methods: National population‐based survey of women and men aged 18-51 years recruited from a random sample of electors on the Australian Electoral Roll in 2013. Data were weighted to reduce non‐response bias. Factors associated with unintended pregnancy were identified in multivariable analyses. Results: Data from 2,235 completed questionnaires were analysed (Women: 69%; Men: 31%). Of those ever pregnant or partner in pregnancy (59%), 40% had experienced an unintended pregnancy. Adjusting for other risks, ever having experienced sexual coercion (AOR, 95%CI=Women 1.948; 1.458-2.601; Men 1.657, 1.014-2.708); socioeconomic disadvantage (AOR, 95%CI=Women 1.808, 1.373, 2.381; Men 1.360, 1.004-1.841), living in a rural area (AOR, 95%CI=Women 1.403, 1.056-1.864; Men 1.583, 1.161-2.159), and for men being born overseas (AOR, 95%CI 1.989, 1.317-3.002) were significantly associated with unintended pregnancy. Conclusions: Experiences of sexual coercion, social disadvantage, rural residence and overseas birth are independently associated with unintended pregnancy in Australia. Implications: Public health policy and health service initiatives should prioritise prevention of sexual coercion, reduction of social inequality and reduction of geographic inequality for those in rural areas.